Gut dysbiosis and the role of probiotics in chronic kidney disease - Cahyadi, Alius; Yuwono, Angelina; Subagio, Stephanie Widodo; Iryaningrum, Maria Riastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Chronic inflammatory condition in chronic kidney disease (CKD) patients is associated with increased risk of cardiovascular morbidity and mortality. Gut dysbiosis is assumed as one of leading factors to the chronic inflammatory condition. The relationship between the kidney and the gastrointestinal, knowns as the gut-kidney axis, has a role in production and accumulation of uremic toxins derived from gut microbial fermentation of protein, and translocation of endotoxins and microbial from gut lumen into bloodstream due to alterations of intestinal epithelial barrier in CKD patients. Probiotics supplementation is one of the optional theraphy to restore the gut dysbiosis in CKD patients. Recent studies found that probiotics supplementation in CKD patients decreased uremic toxins and pro-inflammatory cytokines production, and delayed CKD progression. The improvement of this chronic inflammatory condition is expected to decrease cardiovascular disease risk in CKD patients. This review aims to describe the importance of gut-kidney axis in CKD patients, particularly in gut dysbiosis, and the role of probiotics in progression of CKD.